Author 
Message 
TAGS:

Hide Tags

Senior Manager
Joined: 02 Jan 2017
Posts: 313
Location: Canada

If a + b = x, and a – b = y, then ab =
[#permalink]
Show Tags
25 Feb 2017, 22:58
Question Stats:
77% (01:09) correct 23% (01:37) wrong based on 97 sessions
HideShow timer Statistics
If a + b = x, and a – b = y, then ab = (A) (x^2 – y^2)/2 (B) (x + y)(x – y)/2 (C) (x^2 – y^2)/4 (D) xy/2 (E) (x^2 + y^2)/4
Official Answer and Stats are available only to registered users. Register/ Login.



Senior Manager
Joined: 19 Apr 2016
Posts: 274
Location: India
GMAT 1: 570 Q48 V22 GMAT 2: 640 Q49 V28
GPA: 3.5
WE: Web Development (Computer Software)

Re: If a + b = x, and a – b = y, then ab =
[#permalink]
Show Tags
25 Feb 2017, 23:56
vikasp99 wrote: If a + b = x, and a – b = y, then ab =
(A) x^2 – y^2/2 (B) (x + y)(x – y)/2 (C) x^2 – y^2/4 (D) xy/2 (E) x^2 + y^2/4 a + b = x \((a+b)^2 = x^2\) \(a^2 + b^2 + 2ab = x^2\) I a  b = y \((ab)^2 = y^2\) \(a^2 + b^2  2ab = y^2\) II I  II \(4ab = x^2  y^2\) \(ab = (x^2  y^2)/4\) vikasp99 : Could you please add brackets to the numerators of the options as it will make the options more clear ? Hence option C is correct Hit Kudos if you liked it .



Math Expert
Joined: 02 Sep 2009
Posts: 49251

Re: If a + b = x, and a – b = y, then ab =
[#permalink]
Show Tags
26 Feb 2017, 03:33



Math Expert
Joined: 02 Sep 2009
Posts: 49251

Re: If a + b = x, and a – b = y, then ab =
[#permalink]
Show Tags
26 Feb 2017, 03:34



Manager
Joined: 31 Jan 2017
Posts: 58
Location: India
Concentration: Strategy, Leadership
GPA: 4
WE: Project Management (Energy and Utilities)

Re: If a + b = x, and a – b = y, then ab =
[#permalink]
Show Tags
26 Feb 2017, 07:46
Point to Note: a*b = [(a+b)^2  (ab)^2 ] /4
_________________
__________________________________ Kindly press "+1 Kudos" if the post helped



Senior Manager
Joined: 06 Jan 2015
Posts: 473
Location: India
Concentration: Operations, Finance
GPA: 3.35
WE: Information Technology (Computer Software)

Re: If a + b = x, and a – b = y, then ab =
[#permalink]
Show Tags
26 Feb 2017, 08:18
vikasp99 wrote: If a + b = x, and a – b = y, then ab =
(A) (x^2 – y^2)/2 (B) (x + y)(x – y)/2 (C) (x^2 – y^2)/4 (D) xy/2 (E) (x^2 + y^2)/4 Hi, Squaring on both side \((a + b)^2 = x^2\), and \((a – b)^2 = y^2\) On simplification \(x^2y^2=4ab\) \(ab=(x^2y^2)/4\) Hence C
_________________
आत्मनॊ मोक्षार्थम् जगद्धिताय च
Resource: GMATPrep RCs With Solution



VP
Joined: 07 Dec 2014
Posts: 1087

If a + b = x, and a – b = y, then ab =
[#permalink]
Show Tags
26 Feb 2017, 10:52
vikasp99 wrote: If a + b = x, and a – b = y, then ab =
(A) (x^2 – y^2)/2 (B) (x + y)(x – y)/2 (C) (x^2 – y^2)/4 (D) xy/2 (E) (x^2 + y^2)/4 adding, 2a=x+y subtracting, 2b=xy multiplying, 4ab=(x+y)(xy) ab=(x^2y^2)/4 C



Intern
Joined: 06 Jun 2017
Posts: 6

Re: If a + b = x, and a – b = y, then ab =
[#permalink]
Show Tags
12 Mar 2018, 08:08
Does anybody mind explaining to me why I should automatically think to square "a+b=x" & "ab=y" upon seeing these clues? What about the given information should indicate to a test taker "Ya know what... lets square those clues in order to solve this problem"?



Manager
Joined: 31 Jan 2017
Posts: 58
Location: India
Concentration: Strategy, Leadership
GPA: 4
WE: Project Management (Energy and Utilities)

Re: If a + b = x, and a – b = y, then ab =
[#permalink]
Show Tags
12 Mar 2018, 12:41
aaronhew wrote: Does anybody mind explaining to me why I should automatically think to square "a+b=x" & "ab=y" upon seeing these clues? What about the given information should indicate to a test taker "Ya know what... lets square those clues in order to solve this problem"? [(a+b)^2  (ab)^2 ] = 4*a*b [(a+b)^2 + (ab)^2 ] = a^2 + b^2 These are two of the relevant and standard formula to be at your fingertips. As far as this problem is concerned, asking for the value of a*b is the obvious clue and there is nothing more to research on this problem.
_________________
__________________________________ Kindly press "+1 Kudos" if the post helped



Manager
Joined: 16 Sep 2016
Posts: 240

Re: If a + b = x, and a – b = y, then ab =
[#permalink]
Show Tags
12 Mar 2018, 12:46
\(a+b = x\) \(ab = y\)
when we square both .. we will have the squared terms in positive and the product of a& b term with opposite signs in the two equations.
We can subtract to get rid of the quadratic terms
so 1  2 leads to
\(4ab = x^2  y^2\)
And the answer is C.



Senior SC Moderator
Joined: 22 May 2016
Posts: 1973

If a + b = x, and a – b = y, then ab =
[#permalink]
Show Tags
12 Mar 2018, 14:10
vikasp99 wrote: If a + b = x, and a – b = y, then ab =
(A) (x^2 – y^2)/2 (B) (x + y)(x – y)/2 (C) (x^2 – y^2)/4 (D) xy/2 (E) (x^2 + y^2)/4 aaronhew wrote: Does anybody mind explaining to me why I should automatically think to square "a+b=x" & "ab=y" upon seeing these clues? What about the given information should indicate to a test taker "Ya know what... lets square those clues in order to solve this problem"? aaronhew Hilarious. Levity is good. You may know the algebraic identities but may not have seen the clue. Bunuel lists them here, Algebraic Identities (scroll down)If you draw a blank, another way to answer is to assign values. Let a = 3, b = 2x = (a + b) = (3 + 2) = 5y = (a  b) = (3  2) = 1(ab) = (3*2) = 6Using x = 5 and y = 1, find the answer that yields 6(A) (x^2 – y^2)/2: \(\frac{(5^21^2)}{2}=\frac{24}{2}=12\). NO (B) (x + y)(x – y)/2: \(\frac{(5+1)(51)}{2}=\frac{24}{2}=12\). NO (C) (x^2 – y^2)/4: \(\frac{(5^21^2)}{4}=\frac{24}{4}=6\). MATCH(D) xy/2: \(\frac{(5*1)}{2}=\frac{5}{2}\). NO (E) (x^2 + y^2)/4: \(\frac{(5^2+1^2)}{4}=\frac{26}{4}=\frac{13}{2}\). NO Answer C
_________________
In the depths of winter, I finally learned that within me there lay an invincible summer.  Albert Camus, "Return to Tipasa"




If a + b = x, and a – b = y, then ab = &nbs
[#permalink]
12 Mar 2018, 14:10






